2014
DOI: 10.1002/2013sw001027
|View full text |Cite
|
Sign up to set email alerts
|

GCR environmental models III: GCR model validation and propagated uncertainties in effective dose

Abstract: This is the last of three papers focused on quantifying the uncertainty associated with galactic cosmic rays (GCR) models used for space radiation shielding applications. In the first paper, it was found that GCR ions with Z > 2 and boundary energy below 500 MeV/nucleon induce less than 5% of the total effective dose behind shielding. This is an important finding since GCR model development and validation have been heavily biased toward Advanced Composition Explorer/Cosmic Ray Isotope Spectrometer measurements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 37 publications
(55 reference statements)
0
11
0
Order By: Relevance
“…One source contributing to the uncertainty is the transport of GCRs through the heliosphere. A series of papers in 2014 showed that different transport models can lead to differences of up to 50% in the resulting effective dose [ Slaba and Blattnig , , ; Slaba et al , ]. We leave a detailed analysis of how these different models affect the model's output to a future study.…”
Section: Resultsmentioning
confidence: 99%
“…One source contributing to the uncertainty is the transport of GCRs through the heliosphere. A series of papers in 2014 showed that different transport models can lead to differences of up to 50% in the resulting effective dose [ Slaba and Blattnig , , ; Slaba et al , ]. We leave a detailed analysis of how these different models affect the model's output to a future study.…”
Section: Resultsmentioning
confidence: 99%
“…The limited measurements were shown to lead to a calibration bias, in which the models are found to be reasonably accurate (less than 15% model error) [ NCRP , ] when compared to the available data, but larger differences (>50%) in radiation exposure calculations behind shielding using the GCR models were found [ Mrigakshi et al , ; Slaba and Blattnig , ]. The discovery of the calibration bias has led to more rigorous sensitivity analysis and validation [ Slaba and Blattnig , ; Slaba et al , ]. The validation work will be aided by future improved measurements with the Alpha Magnetic Spectrometer instrument on the International Space Station [ Aguilar et al , ].…”
Section: Galactic Cosmic Ray Modelsmentioning
confidence: 99%
“…radiation exposure calculations behind shielding using the GCR models were found Slaba and Blattnig, 2014a]. The discovery of the calibration bias has led to more rigorous sensitivity analysis and validation [Slaba and Blattnig, 2014b;Slaba et al, 2014]. The validation work will be aided by future improved measurements with the Alpha Magnetic Spectrometer instrument on the International Space Station [Aguilar et al, 2015].…”
Section: Model Calibrationmentioning
confidence: 99%
“…These estimates of risk are based on particle fluences simulated by deterministic radiation transport codes, which are verified and validated by fits to measurements of GCR ion fluences from probes in Earth's atmosphere. The available database for comparison is limited, as the majority of data were collected at energies below 500 AMeV [2]. However, GCR at these energies are limited contributors to effective dose [3].…”
Section: %*(And+*!and%mentioning
confidence: 99%
“…H-1, He-4, and Fe-56 beams were extracted at 0.4 AGeV, while H-1 and Fe-56 were extracted at 0.8 AGeV,. These projectiles were incident on the the center of the primary upstream target, composed of either aluminum with thicknesses of 20, 40, and 60 g/cm 2 and area 30 x 100 cm 2 . A second downstream target was placed 3.5 m from the center of the upstream target.…”
Section: '(!$%* (!-mentioning
confidence: 99%